Understanding adult learners’ perceptions of postsecondary education using stated propensity to attend - Mueller, Julie M.; Lawless, Jessica R. (American Journal of Education and Learning, 2026)
Postsecondary education provides a well-established pathway to economic mobility with positive benefits for the individual and society. However, public confidence in higher education continues to decline in the US, and the value proposition of a postsecondary degree faces considerable challenges. Arizona is one of the fastest-growing states in the country, with one of the lowest levels of postsecondary attainment and over a million adult learners with some college, no degree. Increasing enrollment for adult learners provides the opportunity to bolster postsecondary attainment and meet Arizona’s workforce needs. We predict stated propensity to attend university within the next two years using an online survey with a random sample of adults with a high school diploma and no college degree, aged 18-35 in Arizona, USA. Contrary to results from polls of the entire adult population, we find evidence indicating the value proposition of postsecondary education is intact for adult learners. We also find evidence that perceptions of high cost are not a significant predictor of stated propensity to attend. Our results indicate differences in preferences that can help inform marketing, recruitment, and financial aid policies for the adult learner population.